Are benzodiazepines effective for treatment of generalized anxiety disorder?. Issue 6 (June 2017) - Kalwani, Ravi; Van Buskirk, John
Abstract : EVIDENCE‐BASED ANSWER : Benzodiazepine therapy produces a small reduction in generalized anxiety disorder (GAD) symptoms for up to 8 weeks (SOR: A, based on 2 systematic reviews of RCTs). However, benzodiazepines are not recommended as a treatment for GAD except in short‐term crisis situations (SOR: C, expert opinion).